Cross-Examination and Comparison of Effects of Nutritive and Non-Nutritive Sweeteners on Male Reproductive Health Using Wistar Rat Model (Nigerian Journal of Physiological Sciences, 2024)
Sucrose and saccharin are prevalent sweeteners in today’s diet, playing crucial roles in global food and beverage consumption. The intake of sucrose, a natural sweetener, alongside saccharin, an artificial alternative, has raised various health concerns related to their effects on reproductive health. This study specifically focuses on how these sweeteners influence male reproductive parameters, including sperm quality, hormonal levels (such as Follicle Stimulating Hormone FSH, Luteinizing Hormone LH, and Testosterone), reproductive gene expressions, as well as the functionality of reproductive organs, utilizing animal models (in vivo). By conducting a thorough review of existing literature and experimental studies, this project seeks to assess whether exposure to sucrose and saccharin poses risks to male reproductive functions, while also identifying the mechanisms through which these substances impact male reproductive health. The investigation centers on the effects of sucrose and saccharin on reproductive function in male Wistar rats. Thirty male albino Wistar rats, each weighing between 180-200 grams, were randomly assigned to three groups: Group One served as the control, Group Two received sucrose (100 mg/kg), and Group Three was administered saccharin (5 mg/kg). The findings indicated that levels of Follicle Stimulating Hormone, Luteinizing Hormone, Testosterone, and Steroidogenic Acute Regulatory Protein (StAR) significantly decreased in the sucrose and saccharin groups compared to the control group. Additionally, the testicular antioxidant Malondialdehyde levels increased relative to the control, while Superoxide Dismutase and Catalase levels were significantly decreased. Furthermore, sperm profile—including sperm count, motility, and viability—showed significant alterations when compared to the control group. These results suggest that both sucrose and saccharin can negatively impact reproductive function by diminishing testicular antioxidant activity, altering sperm characteristics (count, motility, and viability), and inhibiting StAR, ultimately leading to testicular damage.Keywords: Sucrose, Saccharin, Sweeteners, Hormonal levels, Sperm quality. Wistar rats